Review of control and fault diagnosis methods applied to coal mills. (August 2015) - Agrawal, V.; Panigrahi, B.K.; Subbarao, P.M.V.
Abstract: Power plant performance and reliability is highly influenced by coal mills that grind, dry, and transport coal to the furnace. This paper presents a review of the current state of technology on improved controls and fault diagnosis methods applied to mills. An understanding of the mill system, control issues and major faults influencing the mill performance are discussed. Control strategies applied for mill controls such as control using estimated pulverized fuel flow and advanced techniques such as decoupling control, predictive control, fuzzy control, self-optimizing control, and some other combined control algorithms are presented. Fault diagnosis techniques for mills are segregated into quantitative, signal, qualitative, and process history based approaches depending on the priori information used for the diagnosis. Comparative study of different control and fault diagnosis techniques applied to the milling system is conducted and possible directions are provided for future research.